2009
DOI: 10.3892/or_00000566
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of MMP-2 and MMP-9 by cytokines, mitogens and inhibitors in lung cancer and malignant mesothelioma cell lines

Abstract: Abstract. Matrix metalloproteinases (MMPs) secreted by lung cancer (LC) and malignant mesothelioma (MM), especially MMP-2 and MMP-9, play crucial roles in tumor invasion and metastasis. We examined the effect of cytokines, mitogens and inhibitors on MMP-2 and MMP-9 expression in LC and MM cell lines. Human LC (A-549) and MM (MSTO-211H) cell lines were cultured in appropriate media. At near confluence, the cells were washed with PBS and incubated in serum-free medium with various concentrations of several cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…32 From in vitro studies, it was found that EGCG inhibited MMP-2 and -9 expressions in human lung cancer A549 cells. 33 Additionally, an inhibitory effect of EGCG on the migration of bronchial tumor cells in 2D and 3D cell culture models has been shown. EGCG treatment also inhibited the expression of MMP-2 in both mRNA and protein levels and altered the intermediate filaments of vimentin.…”
Section: Discussionmentioning
confidence: 96%
“…32 From in vitro studies, it was found that EGCG inhibited MMP-2 and -9 expressions in human lung cancer A549 cells. 33 Additionally, an inhibitory effect of EGCG on the migration of bronchial tumor cells in 2D and 3D cell culture models has been shown. EGCG treatment also inhibited the expression of MMP-2 in both mRNA and protein levels and altered the intermediate filaments of vimentin.…”
Section: Discussionmentioning
confidence: 96%
“…A chronically inflamed microenvironment can be induced either by reactive oxygen/nitrogen species (ROS/RNS) [ 18 ], paracrine factors, or tumor-infiltrating cells, inciting continuous cell proliferation, DNA damage, or cancer transformation [ 19 ]. Inflammatory cytokines [ 20 , 21 , 22 ] and chemokines [ 23 , 24 , 25 ] provide conducive signaling to induce cancer proliferation [ 20 , 26 ] and tumor angiogenesis [ 17 ]. It is well-established that salt induces a chronic inflammatory response [ 27 , 28 ].…”
Section: Salt Induced Tumorigenesismentioning
confidence: 99%
“…Some other studies investigating MMPs in mesothelioma focused on the basic roles of MMPs in tumor invasion and progression [18,19]. Doi et al investigated the expression of MT1-MMP and the invasion ability of the mesothelioma cell line established from a clinical specimen of a patient with mesothelioma.…”
Section: Mmps Expression In Tissue and Body Fluids As Biomarker In Mesotheliomamentioning
confidence: 99%